Dangerous moonlight - Addinsell, Richard 1904-1977 (Odeon Entertainment, 2010)
"During World War II, an American newswoman falls for a Polish piano virtuoso...who wants to go back and fight."[imdb.com]
Original: Großbritannien 1941
Extras: best of British trailers and booklet notes
Bildformat 1.33:1
Keywords: Film; DVD-Video